An Insight into the Current Understanding of Status Epilepticus: From Concept to Management - Khouloud Abdulrhman Al-Sofyani (Neurology Research International)
Status epilepticus (SE), a subset of epilepsy, represents a debilitating neurological disorder often associated with alarming mortality and morbidity numbers. Even though SE is one of the extensively researched topics with conspicuous data available in the literature, a scientific gap exists in understanding the heterogeneous facets of the disorder like occurrence, definition, classification, causes, molecular mechanisms, etc., thereby providing a defined management program. Cognizance of this heterogeneity and scientific limitation with its subsequent correlation to the recent advancements in medical and scientific domains would serve not only in bridging the gap but also in developing holistic and prompt management programs. Keeping this as an objective, an extensive literature survey was performed during this study, and key findings have been shared. The present study provides a semantic and perspective synopsis toward acknowledging the diversified nature of SE and its variants with respect to their definition, classification, etiology, diagnosis, and management.